Leg ulcer service provision in NHS hospitals. (24th February 2022) - Lian, Yaping; Anderson, Irene; Stather, Philip
Abstract : Leg ulcers are painful, distressing and common in the older population. They are costly to treat and put pressure on NHS providers. Compression therapy is the mainstay of treatment of venous leg ulceration. Aim: To explore the service provision for compression therapy for inpatients with leg ulcers in UK hospitals. Methods: An online survey was carried out to explore the service provision in hospital settings. It was distributed to Wounds UK National Conference delegates and to wound care specialist groups using social media. Results: The authors received 101 responses from health professionals in the UK. Of these, 67.3% reported there was no dedicated service for inpatients with leg ulceration and only 32% said compression therapy was provided in their hospitals. Conclusion: This survey confirmed there is a significant shortfall in care provision for patients with leg ulcers in secondary care and highlighted the wide variations in service delivery in hospitals. Further research is needed to understand the reasons for these variations.